Model-based approach for specifying requirements of virtual reality software products - Sai Anirudh Karre; Y. Raghu Reddy (Frontiers in Virtual Reality)
IntroductionGathering requirements for developing virtual reality (VR) software products is a labor-intensive process. It requires detailed elicitation of scene flow, articles in the scene, action responses, custom behaviors, and timeline of events. The slightest change in requirements will escalate the design and development costs. While most VR practitioners depend on conventional software engineering (SE) requirement-gathering techniques, there is a need for novel methods to streamline VR software development. With severe software platform fragmentation and hardware volatility, VR practitioners need assistance specifying non-volatile requirements for a minimum viable VR software product.MethodsTo address this gap, we present virtual reality requirement specification tool (VReqST), a model-based requirement specification tool for developing virtual reality software products.ResultsUsing VReqST, requirement analysts can specify the requirements for both simple and complex multi-scene VR software products and virtual environments (VEs).DiscussionVReqST is customizable and competent in illustrating custom requirements for new locomotion, colocation, teleportation algorithms, etc. We worked with the VR community from the industry for adoption and feedback. We revised and included the desired features based on inputs from the VR community and gathered their observations on the overall impact of VReqST in practice.